FLOTASI KASITERIT DARI BIJIH TIMAH PRIMER TIPE SKARN ASAL PULAU BELITUNG - Kamoda, Rustam; Sanwani, Edy (Jurnal Teknologi Mineral dan Batubara, 2023)
Indonesia as one of the world's tin producers, not only has tin reserve from secondary deposit, but also has tin reserve from skarn-type primary deposit located on Belitung Island. The presence and characteristics of cassiterite in skarn-type of primary tin ore can be confirmed through sample characterization and have the potential to be separated from impurity minerals by flotation method. There are several factors that can affect the separation of valuable mineral from impurities through the flotation method, namely minerals association, the use of collector type scheme, pH condition of flotation and the use of depressant. The result of sample characterization showed that the primary tin ore of the skarn type from Belitung Island contained Sn in a low concentration of 0.1615% in the form of cassiterite. The flotation experiments carried out in two schemes. The first scheme was flotation on samples using SHA, SO and SHA + SO as collectors in the different pH values (pH 6, 7, 8, and 9) and flotation with the absence and presence of depressant at pH 8 for each type of collector. Recovery, grade, percent mass pull, enrichment ratio, separation efficiency, and selectivity index were the parameters used to assess flotation performance. Generally, the experimental results showed that cassiterite flotation in different pH values tend to show a better performance at pH 8. The flotation results of the three type of collectors showed that the recovery of Sn from SHA collector < SO < SHA+SO. In term of grade in the concentrate, the Sn grade of SO < SHA+SO < SHA collector. Flotation experiments from the three type of collectors in the absence and presence of depressant showed that flotation performance was better in the absence of depressant.